Developing a Collaborative Learning Environment For ITS: A New Model Based on IMS-Learning Design (Statistics, Optimization & Information Computing, 2024)
Intelligent Tutoring Systems (ITS) represent a significant advancement in educational technology, evolving from computer-assisted teaching to more adaptive and interactive learning environments. This paper aims to delve into the methodological aspects of collaborative ITS, with a particular focus on the integration of IMS Learning Design (IMS-LD). The objective is to explore how IMS-LD is instrumental in designing and managing ITS and addressing the challenges of modern education systems. The proposed model addresses these challenges through three foundational principles: categorizing learning activities, clearly defining roles, and designating specific spaces for diverse activities. By integrating the learner model and IMS-LD, the model aims to enhance personalization and effectiveness, creating a more efficient, learner-centric system. The paper also discusses the development of meta-models for collaborative ITS, their correspondence with IMS-LD, and the challenges and benefits of model transformation techniques. The findings highlight the potential of ITS in providing adaptive and personalized learning experiences, fostering effective communication and collaboration among participants, and enhancing the overall quality of education through innovative technological integration.